2008
DOI: 10.1080/10236660802351409
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Green Coconut Fiber Composites

Abstract: Resumo: Compósitos de polipropileno com 10, 20 e 30% em volume de fibra de coco verde foram obtidos em câmara de mistura Haake, tendo como variáveis a temperatura de processamento e a velocidade de cisalhamento. O módulo de flexão e as características morfológicas dos diferentes compósitos obtidos foram avaliados e comparados com o polipropileno puro. Foi observado que a temperatura de 170 °C, a velocidade do rotor de 60rpm e o teor de fibra de coco verde de 30% forneceram o melhor desempenho quanto à flexão. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For the preparation of the aforementioned products, tender coconut husk has to be removed by manual or mechanical means. Researchers have reported that tender coconut husk weight constitutes about 85% of the fruit weight (Ishizaki, Visconte, Furtado, de Oliveira, & Leblanc, ). To the best of our knowledge, limited numbers of commercial machines are available for mechanical chopping and/or trimming of tender coconut because of its hard nature.…”
Section: Introductionmentioning
confidence: 99%
“…For the preparation of the aforementioned products, tender coconut husk has to be removed by manual or mechanical means. Researchers have reported that tender coconut husk weight constitutes about 85% of the fruit weight (Ishizaki, Visconte, Furtado, de Oliveira, & Leblanc, ). To the best of our knowledge, limited numbers of commercial machines are available for mechanical chopping and/or trimming of tender coconut because of its hard nature.…”
Section: Introductionmentioning
confidence: 99%
“…The composites made up of renewable soy protein based resins and high strength liquid crystalline cellulose fibers [12] and jute reinforced biodegradable Nano-bio composite using soy milk as matrix and Nano clay as additive [13] are recently invented and their properties were studied. Marina et al studied the characterization of Green Coconut Fiber Composites [14].…”
Section: Introductionmentioning
confidence: 99%